The Effect of Balance Exercises on Success Level of Air Pistol Shooters - Ahmet Serhat Aydın; Serkan Revan (Selcuk University, 2020)
The aim of this study is to research the effects of air pistol balance shootings on shooting success, which performed for 12 weeks with certain air pistol shooters. 49 volunteer shooters has participated in the shootings, which composed of 25 women between 15-17 ages (n=13 experiment, n=12 control) and 24 men (n=12 experiment, n=12 control) from three shooting sports club in Ankara. While the experiment and control groups continued shooting trainings, experiment groups were practised balance exercises with bosu ball three times a week during 12 weeks following the shooting training. SPSS 23 package program was used in the analysis of the obtained data. In order to determine whether the data showed normal distribution, normality analysis was conducted and the distribution was found to be normal. The comparison of the control and experimental groups were analyzed by independent sample t test and the pre- and post-test comparisons were analyzed by paired sample t test. Pearson correlation analysis was used to determine the relationship between achievement score and static and dynamic balance. In the statistical analyzes used in the research, the significance level was accepted as 0.05 and 0.001. At the end of 12 weeks, on both women and men experiment and balance groups, significant differences were detected between dynamic balance pre-test and post-test results (p lt;0,05). As for the static balance results of both genders, only on the experiment groups considerable differences were found (p lt;0,001). As a result of the study it can be concluded that the balance exercises practiced for 12 weeks have affected the shooting performance positively by improving static and dynamic balance.